Do Experts incorporate Statistical Model Forecasts and should they? - Rianne Legerstee; Philip Hans Franses; Richard Paap (Tinbergen Institute, 2011)
Experts can rely on statistical model forecasts when creating their own forecasts. Usually it is not known what experts actually do. In this paper we focus on three questions, which we try to answer given the availability of expert forecasts and model forecasts. First, is the expert forecast related to the model forecast and how? Second, how is this potential relation influenced by other factors? Third, how does this relation influence forecast accuracy? We propose a new and innovative two-level Hierarchical Bayes model to answer these questions. We apply our proposed methodology to a large data set of forecasts and realizations of SKU-level sales data from a pharmaceutical company. We find that expert forecasts can depend on model forecasts in a variety of ways. Average sales levels, sales volatility, and the forecast horizon influence this dependence. We also demonstrate that theoretical implications of expert behavior on forecast accuracy are reflected in the empirical data.
urn:NBN:nl:ui:15-1765/26526
Keywords: C11; C53; 330; model forecasts; expert forecasts; forecast adjustment; Bayesian analysis; endogeneity; Pharmazeutisches Produkt; Absatz; Prognoseverfahren; Sachverständige; Vergleich; Bayes-Statistik